Fixed-time artificial insemination in buffalo - G. A. Crepaldi; L. U. Gimenes; N. A.T. Carvalho; P. S. Baruselli (Italian Journal of Animal Science, 2010)
Artificial insemination (AI) in buffalo has limited use worldwide due the difficulties in the estrus detection and in finding an adequate moment for this procedure. Therefore, an alternative to increase the number of buffalo that are inseminated is the use of protocols that allow the AI without the need of estrus detection, usually called fixed-time AI (FTAI). Our expanding knowledge of the control of follicular wave dynamics during the buffalo estrous cycle has resulted in renewed enthusiasm for the prospects of precisely control of the follicular and luteal dynamics and finely controlling the time of ovulation. Follicular wave development can be controlled by treatments with GnRH or estradiol and progestogen/progesterone in combination. Treatment of buffalo with GnRH in combination with prostaglandin F2α (PGF2α) 7 d later and a second GnRH 48 h after PGF2α (known as Ovsynch) has resulted in acceptable pregnancy rates after FTAI in cycling buffalo during the breeding season. FTAI protocols using progestin devices, estradiol and eCG have resulted in synchronous onset of a new follicular wave, synchronous ovulation and consistent pregnancy rates in anestrous buffalo during the off breeding season. The combination of these protocols permits the use of AI throughout the year, obtaining conception and calving even in anestrus buffalo during the off breeding season.